Dissecting aid fragmentation: Development goals and levels of analysis - Ruth D. Carlitz; Sebastian Ziaja (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Aid fragmentation is widely denounced, though recent studies suggest potential benefits. To reconcile these mixed findings, we make a case for studying differences across aid sectors and levels of analysis. Our cross-national time-series analysis of data from 141 countries suggests aid fragmentation promotes child survival and improves governance. However, just looking across countries has the potential to blur important within-country differences. We analyse subnational variation in Sierra Leone and Nigeria and find that the presence of more donors is associated with worse health outcomes, but better governance outcomes. This suggests that having more donors within a locality can be beneficial when they are working to improve the systems through which policies are implemented, but harmful when they target policy outcomes directly. A survey of Nigerian civil servants highlights potential mechanisms. Fragmentation in health aid may undermine civil servants' morale, whereas diversity in governance aid can promote meritocratic behaviour.
Keywords: 330; Entwicklungshilfe; Gesundheitsversorgung; Good Governance; Sierra Leone; Nigeria; Welt